2017
DOI: 10.1160/th16-10-0748
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin clot structure - pro-fibrinolytic effect of oral contraceptives in apparently healthy women

Abstract: Fibrin metabolism is influenced by many factors. The velocity of fibrin formation, genetic polymorphisms, fibrinolytic features and the structure of the fibrin clot are determinants of fibrin turnover. Oral contraceptives (OCs) have significant impact on the haemostatic system, by increasing the concentration of coagulation factors, plasminogen and tissue plasminogen activator activity, and decreasing the concentration of haemostatic inhibitors. The present study addresses the influence of OCs on fibrin struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We have previously shown that women with atrial fibrillation differ in fibrin polymerization characteristics compared to men [ 18 ] and that women receiving OC have alterations in fibrin structure and increased clot lysability [ 31 ]. Moreover, middle-aged women receiving estrogen therapy have a reduced burden of CAC compared to women receiving placebo [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that women with atrial fibrillation differ in fibrin polymerization characteristics compared to men [ 18 ] and that women receiving OC have alterations in fibrin structure and increased clot lysability [ 31 ]. Moreover, middle-aged women receiving estrogen therapy have a reduced burden of CAC compared to women receiving placebo [ 32 ].…”
Section: Discussionmentioning
confidence: 99%